Topologically enhanced harmonic generation in a nonlinear transmission line metamaterial - You Wang (Nature Portfolio, 2019)
Higher harmonic generation can be enhanced in left-handed nonlinear transmission lines. Here Wang et al. show that the presence of a topological edge state in a circuit analogue of the Su-Schrieffer-Heeger model can increase this enhancement even further.